International consensus recommendations for target volume delineation specific to sacral metastases and spinal stereotactic body radiation therapy (SBRT) - Dunne, Emma M.; Sahgal, Arjun; Lo, Simon S.; Bergman, Alanah; Kosztyla, Robert; Dea, Nicolas; Chang, Eric L.; Chang, Ung-Kyu; Chao, Samuel T.; Faruqi, Salman; Ghia, Amol J.; Redmond, Kristin J.; et al. (Radiotherapy and oncology, 2020)
•SBRT contouring recommendations for metastatic disease to the sacrum have been established.•High degree of agreement in target delineation among spine SBRT experts.•Critical first step to standardisation of target delineation practice in the sacrum.•The sacral classification system (SCS) guides the anatomic description of contours.•The SCS will help serve as a framework for future pattern of failure analyses. To interrogate inter-observer variability in gross tumour volume (GTV) and clinical target volume (CTV) delineation specific to the treatment of sacral metastases with spinal stereotactic body radiation therapy (SBRT) and develop CTV consensus contouring recommendations. Nine specialists with spinal SBRT expertise representing 9 international centres independently contoured the GTV and CTV for 10 clinical cases of metastatic disease within the sacrum. Agreement between physicians was calculated with an expectation minimisation algorithm using simultaneous truth and performance level estimation (STAPLE) and with kappa statistics. Optimised confidence level consensus contours were obtained using a voxel-wise maximum likelihood approach and the STAPLE contours for GTV and CTV were based on an 80% confidence level. Mean GTV STAPLE agreement sensitivity and specificity was 0.70 (range, 0.54–0.87) and 1.00, respectively, and 0.55 (range, 0.44–0.64) and 1.00 for the CTV, respectively. Mean GTV and CTV kappa agreement was 0.73 (range, 0.59–0.83) and 0.59 (range, 0.41–0.70), respectively. Optimised confidence level consensus contours were identified by STAPLE analysis. Consensus recommendations for the CTV include treating the entire segment containing the disease in addition to the immediate adjacent bony anatomic segment at risk of microscopic extension. Consensus recommendations for CTV target delineation specific to sacral metastases treated with SBRT were established using expert contours. This is a critical first step to achieving standardisation of target delineation practice in the sacrum and will serve as a baseline for meaningful pattern of failure analyses going forward.